Percutaneous Treatment of Superficial Femoral Artery Total Occlusions: Single Center Experience - ATEŞ, AHMET HAKAN; ÖZBALCI, AYSU BAŞAK; KUL, SELİM and YENERÇAĞ, MUSTAFA and Okşul, Metin and ARSLAN, UĞUR (Acta Medica, 2019)
Objectives Superficial femoral artery (SFA) is the most commonly effected vessel in peripheral arterial disease (PAD) and SFA total occlusions constitute the 50% of PAD patients presenting with symptoms. In this study, we investigated our patients with SFA total occlusions who were treated with percutaneous treatment strategy. Methods In this study, we included ambulatory patients who were admitted to our clinics due to symptomatic severe SFA total occlusion and underwent PTA or PTA + stenting procedure.The demographic findings of the patients, procedure details, complications and follow-up results were noted. Results Out of 67 patients, 62 (92.5%) underwent PTA or PTA + stenting procedure successfully for SFA total occlusions. Only one serious complication, acute renal failure resulting in death developed during hospitalization. The mean follow-up time after the procedure was 11.1±7.2 months. During this follow-up time 36 (58.1%) were asymptomatic. Out of 26 patients who were symptomatic, only 6 of them underwent reintervention and 3 were recommended surgical intervention. Conclusion Peripheral interventions for SFA total occlusions are being performed successfully in experienced centers with low complication rates as the first treatment strategy in PAD. Herein,we have presented our patients who underwent successful PTA and/or stenting procedure with high success and low complication rates. Peripheral interventions should be the first choice for SFA total occlusions in experienced centers.